Is Remakuda Juice Effective to Elevate Haemoglobin Level and Descend Dysmenorrhea in Female Adolescents? - Fatmawati, Zeny; Fatmawati, Elis; Rustanti, Elly (Journal of Maternal and Child Health, 2021)
Background: The negative effect of low hemoglobin levels for adolescents can reduce intelligence, learning achievement, mental motor development, inhibition of optimal height growth and reproductive health. Dysmenorrhea is pain or discomfort that occurs in the abdomen during menstruation as a result of prostaglandin secretion which can increase uterine contractions. The purpose of this study was to determine the effect of Remakuda juice on an increase in hemoglobin and a decrease in the intensity of dysmenorrhea in female adolescents. Subjects and Method: An experimental study with no control group was conducted at Junior High School I Tembelang, Jombang, East Java, in September 2021. A total of 60 female adolescents was selected by purposive sampling. The dependent variables were hemoglobin level and dysmenorrhea. The independent variable was Remakuda juice. Dysmenorrhea was measured by the Numeric Rating Scale (NRS) and the Wong Baker Pain Rating Scale. Hemoglobin level was measured by digital haemometer. The data were analyzed using t-test. Results: Hemoglobin levels after intervention (Mean= 2.00; SD= 0.00) were higher than before (Mean= 1.73; SD= 0.45), with p= 0.010. Dysmenorrhea after intervention was lower (Mean= 1.43; SD= 0.59) than before (Mean= 2.70; SD= 0.65), with p<0.001. Canclusion: Remakuda juice can increase hemoglobin levels and reduce dysmenorrhea in female adolescent.